Efficacy of Iron Tablet Supplementation on Hemoglobin Levels in Adolescents: A Systematic Review - Nanda, Elma; Maryana, Nina; Fadilah, Miftah; Fauzia, Aulia Ridla; Nurapandi, Adi; Marliany, Heni (Inspirasi Foundation, 2025)
Introduction: Iron deficiency anemia is one of the most common nutritional problems among adolescents and can significantly affect physical growth, cognitive development, and overall health. Iron tablet supplementation is widely recognized as a primary intervention to increase hemoglobin levels and prevent anemia in this population. Objective: This study aims to evaluate the effectiveness of iron tablet supplementation in increasing hemoglobin levels among adolescents with anemia. Method: A systematic literature review was conducted using four databases: PubMed, JSTOR, ProQuest, and Garuda. The review included studies published between 2019 and 2025 that examined iron tablet supplementation in adolescents diagnosed with anemia. Hemoglobin levels were assessed before and after supplementation to determine effectiveness. Study selection, data extraction, and quality appraisal were performed independently by two reviewers following the PRISMA guidelines and using the CASP checklist. Results: Four studies involving a total of 430 adolescent participants met the inclusion criteria. All included studies reported a significant increase in hemoglobin levels following daily iron tablet supplementation, particularly among adolescent girls. One month of supplementation was found to be effective in reducing the prevalence of anemia. Conclusion: Iron tablet supplementation is an effective intervention for increasing hemoglobin levels and reducing the incidence of anemia in adolescents. These findings support the continued use of iron supplementation programs as a public health strategy to improve adolescent health and prevent long-term complications associated with iron deficiency anemia.